Analysis of the Multilevel Impact of Social Network Quality on Personality Dimensions in Purchasing - Maryam Akhavan Kharazian; Sona Shafieirad (‫مدیریت بازرگانی)
Objective In today’s rapidly growing era of internet and mobile technology, customers can shop anytime and anywhere. Increased online shopping due to various marketing strategies has led to impulsive and addictive unplanned purchases. Consequently, behaviors related to impulsive buying and compulsive shopping have caught the attention of marketing researchers. This study aims to analyze and examine the multilevel impact of social network quality at the community level on the relationship between personality dimensions and impulsive and compulsive buying.